Self-Propulsion Factors for Minimum Propulsion Power Assessment in Adverse Conditions - Joon-Hyoung Lee; Seunghyun Hwang; Young-Yeon Lee; Woo-Seok Jin; Moon-Chan Kim (Journal of Marine Science and Engineering)
Considering that slow steaming requires low engine power, which impedes maneuverability under severe sea conditions, the International Maritime Organization (IMO) provides guidelines for the minimum propulsion power (MPP) required to maintain ship maneuverability in adverse conditions. This study focused on the characteristics of self-propulsion factors in the context of MPP assessment to enhance MPP prediction accuracy. Overload tests were conducted at low speeds of advance, considering added resistance in adverse conditions. Moreover, propeller open-water tests were conducted corresponding to propeller flow with low Reynolds numbers to investigate their effect on self-propulsion factors. In addition, computational fluid dynamics (CFD) simulations were conducted to analyze physical phenomena such as the flow field and pressure distribution under model test conditions. The results indicated that the thrust deduction factor was lower than that given in the guidelines, whereas the wake fraction was higher at the required forward speed of 2 knots. The MPP assessment in this study revealed that the required brake power was 4–5% lower than that given in the guidelines, indicating that the guidelines need reviewing for a more reliable assessment.